2012
DOI: 10.18352/ijc.299
|View full text |Cite
|
Sign up to set email alerts
|

Managing contested greenspace: neighborhood commons and the rise of dog parks

Abstract: Dog parks present an emerging class or urban environmental amenities. In order to develop a better understanding of dog parks, this article applies existing literature regarding urban parks and common pool resource (CPR) management to off-leash recreation areas. We develop a typology dog-park management and build upon a survey of 298 dog park users of a major dog park. We test the relationship between the perception of the park as a successfully governed CPR, and behaviour which contributes to collective actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 11 publications
0
15
0
2
Order By: Relevance
“…In a random telephone survey in Calgary, Alberta, older adults (over 50 years of age) who frequently walk their dog reported more positive feelings about their neighborhoods and an enhanced sense of community [ 21 ]. Similarly, in observational studies in Texas, Florida, and Georgia, community members reported off-leash dog parks increased socialization with neighbours and created a heightened sense of community [ 6 , 31 ]. Wood and colleagues (2007) described a “ripple effect” of dog ownership and associated park use on neighborhood interactions and sense of community that could extend beyond dog owners to the broader community [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a random telephone survey in Calgary, Alberta, older adults (over 50 years of age) who frequently walk their dog reported more positive feelings about their neighborhoods and an enhanced sense of community [ 21 ]. Similarly, in observational studies in Texas, Florida, and Georgia, community members reported off-leash dog parks increased socialization with neighbours and created a heightened sense of community [ 6 , 31 ]. Wood and colleagues (2007) described a “ripple effect” of dog ownership and associated park use on neighborhood interactions and sense of community that could extend beyond dog owners to the broader community [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, taking a dog out for a walk can enhance the physical activity level of its owner (Cutt, Giles-Corti, Knuiman, Timperio, & Bull, 2008). On the other hand, unattended dogs may deter other people who are scared of pets from undertaking physical activities (Matisoff & Noonan, 2012). If dogs are allowed to be kept within residential neighborhoods, it is necessary to set up dog zones or dog parks (Lee, Shepley, & Huang, 2009) to let people know where they can unleash their dogs and where they need to constrain their pets.…”
Section: Reducing Fear Of Injury Accident and Dog Attacksmentioning
confidence: 99%
“…The reasons why people access the island's trails may be non-rival or non-subtractable in a conventional sense, but this is only the case under conditions where crowding is low and users co-exist in relative harmony (Matisoff and Noonan 2012). TI usage has the potential to become rival where conflicts among users persist, where physical infrastructure is added or environmental quality deteriorates due to overuse, and when institutional conformance is not enforced.…”
Section: Discussionmentioning
confidence: 99%